(3TQM eNJUQ CHj LYaQ GdWMGhis - (3CMeO Hf Ydj GdnqQGRj, CHh HcQ GdLUGU,J (B370 (3g` s; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s ((3Ydi Hf eMeO GdQhGOi s)
(3ChdgG (B:s
(3GdcdGe Ydi MO GdSGQb s
(3GdfSNI HgG MhGTs
(3HgG NQe ef ChdgG ebOGQg (B25 (3hQbIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfajs